Cost savings associated with 10 years of road safety policies in Catalonia, Spain - Anna GarcÃa-Altes; Josep M Suelves; Eneko BarberÃa (The World Health Organization, 2013)
OBJECTIVE: To determine whether the road safety policies introduced between 2000 and 2010 in Catalonia, Spain, which aimed primarily to reduce deaths from road traffic collisions by 50% by 2010, were associated with economic benefits to society. METHODS: A cost analysis was performed from a societal perspective with a 10-year time horizon. It considered the costs of: hospital admissions; ambulance transport; autopsies; specialized health care; police, firefighter and roadside assistance; adapting to disability; and productivity lost due to institutionalization, death or sick leave of the injured or their caregivers; as well as material and administrative costs. Data were obtained from a Catalan hospital registry, the Catalan Traffic Service information system, insurance companies and other sources. All costs were calculated in euros (â,¬) at 2011 values. FINDINGS: A substantial reduction in deaths from road traffic collisions was observed between 2000 and 2010. Between 2001 and 2010, with the implementation of new road safety policies, there were 26 063 fewer road traffic collisions with victims than expected, 2909 fewer deaths (57%) and 25 444 fewer hospitalizations. The estimated total cost savings were around â,¬18 000 million. Of these, around 97% resulted from reductions in lost productivity. Of the remaining cost savings, 63% were associated with specialized health care, 15% with adapting to disability and 8.1% with hospital care. CONCLUSION: The road safety policies implemented in Catalonia in recent years were associated with a reduction in the number of deaths and injuries from traffic collisions and with substantial economic benefits to society.